2021
DOI: 10.1002/andp.202100285
|View full text |Cite
|
Sign up to set email alerts
|

Possible Polarization Measurements in Elastic Scattering at the Gamma Factory Utilizing a 2D Sensitive Strip Detector as Dedicated Compton Polarimeter

Abstract: For photon energies from several 10 keV up to a few MeV Compton polarimetry is an indispensable tool to gain insight into subtle details of fundamental atomic radiative processes. Within the SPARC collaboration several segmented semiconductor detectors are developed that are well suited for application as efficient Compton polarimeters. In this report, these recent developments are reviewed and it is discussed how Compton polarimetry can be employed at the upcoming Gamma Factory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, the dependence on the azimuthal angle ϕ can be observed when utilizing linearly polarized incident radiation. Such radiation can be induced and investigated by dedicated polarimeters [30][31][32] and, moreover, is usually available at synchrotron radiation facilities [33][34][35][36].…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…In contrast, the dependence on the azimuthal angle ϕ can be observed when utilizing linearly polarized incident radiation. Such radiation can be induced and investigated by dedicated polarimeters [30][31][32] and, moreover, is usually available at synchrotron radiation facilities [33][34][35][36].…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…The detector shown in Fig. 3(a) was constructed within the SPARC collaboration for this purpose as a dedicated Compton polarimeter [15]. Up to now it consists of a lithium-diffused silicon crystal allowing an efficient use of the detector for photon energies up to 200 keV.…”
Section: Pos(pstp2022)028mentioning
confidence: 99%
“…Recently, great progress has been achieved in the development of polarization-sensitive X-ray detectors. In particular, state-of-the-art solid-state Compton scatterers allow for a highly precise determination of the linear polarization of photons in the energy range between about 60 keV up to 1 MeV [1,2]. It was shown that the uncertainty of the polarization reconstruction using such polarimeters is mainly limited by the statistics of registered Compton scattering events in the detector and can be reduced to below 1% [3].…”
Section: Introductionmentioning
confidence: 99%